2020
DOI: 10.1515/humor-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

When is it OK to Joke? Adding humor to fear-based colonoscopy screening messages may increase compliance

Abstract: Large scale campaigns frequently use humor to increase compliance with colonoscopy screening recommendations. Problematically, we know little about how humor functions to influence screening. This study seeks to understand whether and how messages framed using humor appeals function differently from those using fear appeals to increase colonoscopy intentions. An online experiment (N = 186) was conducted comparing colonoscopy screening messages framed with a fear appeal and mixed humor/fear appeal. The addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Our data suggest that some people may be turning to Facebook for 'lighter content'; as such, planners may wish to avoid any fear-based messaging. Interestingly, Carcioppolo et al [33] explored the addition of humour to fear-based messages about colonoscopy screening and tested these online using Amazon's Mechanical Turk platform. The authors found that messages with a mixed appeal (fear and humour combined) may be more effective at increasing screening intentions than fear-based messaging alone among those with high cancer worry [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that some people may be turning to Facebook for 'lighter content'; as such, planners may wish to avoid any fear-based messaging. Interestingly, Carcioppolo et al [33] explored the addition of humour to fear-based messages about colonoscopy screening and tested these online using Amazon's Mechanical Turk platform. The authors found that messages with a mixed appeal (fear and humour combined) may be more effective at increasing screening intentions than fear-based messaging alone among those with high cancer worry [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Carcioppolo et al [33] explored the addition of humour to fear-based messages about colonoscopy screening and tested these online using Amazon's Mechanical Turk platform. The authors found that messages with a mixed appeal (fear and humour combined) may be more effective at increasing screening intentions than fear-based messaging alone among those with high cancer worry [33]. This may suggest that the addition of humour may soften fear-based messaging that may otherwise scare the target audience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies used other educational interventions for screening education; a video (n = 2) ( Carcioppolo et al, 2020 , Lucas et al, 2021 ), Facebook promotion (n = 1) ( Lee-Won et al, 2017 ), audio (n = 1) ( Kennedy et al, 2018 ), online education (n = 2) ( Lucas et al, 2016 , Lucas et al, 2018 ), Facebook group (n = 1) ( Key et al, 2020 ), decision aid (n = 3) ( Gabel et al, 2020 , Woudstra et al, 2019 , Housten et al, 2020 ), theatre play (n = 1) ( Friedman et al, 2019 ), women’s health day (n = 1) ( McBride and Gesink, 2018 ), text message (n = 1) ( Alber and Glanz, 2018 ), online message (n = 2) ( Champion et al, 2018 , Neil et al, 2022 ), patient navigation (n = 1) ( Fernandez et al, 2022 ), and a newsletter (n = 2) ( Shepherd et al, 2022 , Leone et al, 2016 ). Five studies measured screening uptake ( Shepherd et al, 2022 , Leone et al, 2016 , Gabel et al, 2020 , Key et al, 2020 , Champion et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Varied intervention formats compared the framing of messages to improve screening intentions or uptake including video (n = 2) ( Carcioppolo et al, 2020 , Lucas et al, 2021 ), Facebook promotion (n = 1) ( Lee-Won et al, 2017 ), and an online education module (n = 2) ( Lucas et al, 2016 , Lucas et al, 2018 ). Loss-framed messaging consistently improved screening uptake or intentions in five studies ( Carcioppolo et al, 2020 , Lee-Won et al, 2017 , Lucas et al, 2021 , Lucas et al, 2016 , Lucas et al, 2018 ) and was more effective compared to gain-framed messaging. Facebook promotion study ( Lee-Won et al, 2017 ) and a video study ( Carcioppolo et al, 2020 ) both found loss-framed messaging was associated with colonoscopy intentions through inducing fear.…”
Section: Resultsmentioning
confidence: 99%